2016
DOI: 10.1016/j.cell.2016.02.035
|View full text |Cite
|
Sign up to set email alerts
|

The CASTOR Proteins Are Arginine Sensors for the mTORC1 Pathway

Abstract: Amino acids signal to the mTOR complex I (mTORC1) growth pathway through the Rag GTPases. Multiple distinct complexes regulate the Rags, including GATOR1, a GTPase activating protein (GAP), and GATOR2, a positive regulator of unknown molecular function. Arginine stimulation of cells activates mTORC1, but how it is sensed is not well understood. Recently, SLC38A9 was identified as a putative lysosomal arginine sensor required for arginine to activate mTORC1 but how arginine deprivation represses mTORC1 is unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
565
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 656 publications
(577 citation statements)
references
References 51 publications
8
565
0
4
Order By: Relevance
“…Amino acids stimulate the mTOR pathway, and amino acid pools rely on glutamine to be maintained. Specifically, arginine and leucine are two amino acids that can together almost fully stimulate mTOR complex 1 (mTORC1) through activation of the RAS-related GTPase (RAG) complex, which in turn recruits mTORC1 to the lysosome and stimulates its activity 72,133,216 . Glutamine can contribute to mTORC1 activation by being exchanged for essential amino acids, including leucine, through the large neutral amino acid transporter 1 (LAT1; a heterodimer of SLC7A5 and SLC3A2) transporter 17 .…”
Section: Key Pointsmentioning
confidence: 99%
“…Amino acids stimulate the mTOR pathway, and amino acid pools rely on glutamine to be maintained. Specifically, arginine and leucine are two amino acids that can together almost fully stimulate mTOR complex 1 (mTORC1) through activation of the RAS-related GTPase (RAG) complex, which in turn recruits mTORC1 to the lysosome and stimulates its activity 72,133,216 . Glutamine can contribute to mTORC1 activation by being exchanged for essential amino acids, including leucine, through the large neutral amino acid transporter 1 (LAT1; a heterodimer of SLC7A5 and SLC3A2) transporter 17 .…”
Section: Key Pointsmentioning
confidence: 99%
“…Binding to Raptor requires RagA/B to be GTP loaded, while RagC/D must be GDP loaded. Nutrients are thought to induce the RagA/B GTP -RagC/D GDP active state via a series of dedicated sensors that, in turn, control GTPase Activating Proteins (GAPs) and guanine nucleotide exchange factors (GEFs) specific for either Rag component (Bar-Peled et al, 2012;Barad et al, 2015;Chantranupong et al, 2016;Saxton et al, 2016;Wolfson et al, 2016;Zoncu et al, 2011). For example, the Gator1 complex has been shown to function as a GAP that promotes GTP hydrolysis by RagA/B, thus causing mTORC1 detachment from the lysosome when nutrient levels are low Panchaud et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid sensors that function upstream of GATOR2 were identified in 2016, that is, Sestrin1/2 as a Leu sensor [52] and CASTOR as an Arg sensor [53]. Previous studies reported that Sestrins interacted with GATOR2 in order to inhibit mTORC1 signaling under amino aciddepleted conditions [54][55][56].…”
Section: Upstream Modules Of Gator2 (Sestrins and Castor)mentioning
confidence: 99%
“…CASTOR1 forms a homodimer with CASTOR1 and a heterodimer with CASTOR2, a CASTOR1-related protein. Arginine specifically binds to CASTOR1 with a dissociation constant of~30 μM, and the binding of Arg to CASTOR1 disrupts the CASTOR1-GATOR2 interaction, which turns CASTOR1 into a homodimer [53]. Liberated GATOR2 interacts with GATOR1 in order to inhibit its GAP activity toward RagA/RagB, which leads to the activation of mTORC1 (Figure 2).…”
Section: Upstream Modules Of Gator2 (Sestrins and Castor)mentioning
confidence: 99%